Potential therapeutic effects of long-term stem cell administration: impact on the gene profile and kidney function of PKD/Mhm (Cy/+) rats - Nardozi, Daniela; Palumbo, Stefania; Khan, Arif ul Maula; Sticht, Carsten; Bieback, Karen; Sadeghi, Samar; Kluth, Mark Andreas; Keese, Michael; Gretz, Norbert (Journal of Clinical Medicine, 2022)
Cystic kidney disease (CKD) is a heterogeneous group of genetic disorders and one of the most common causes of end-stage renal disease. Here, we investigate the potential effects of long-term human stem cell treatment on kidney function and the gene expression profile of PKD/Mhm (Cy/+) rats. Human adipose-derived stromal cells (ASC) and human skin-derived ABCB5+ stromal cells (2 × 106) were infused intravenously or intraperitoneally monthly, over 6 months. Additionally, ASC and ABCB5+-derived conditioned media were administrated intraperitoneally. The gene expression profile results showed a significant reprogramming of metabolism-related pathways along with downregulation of the cAMP, NF-kB and apoptosis pathways. During the experimental period, we measured the principal renal parameters as well as renal function using an innovative non-invasive transcutaneous device. All together, these analyses show a moderate amelioration of renal function in the ABCB5+ and ASC-treated groups. Additionally, ABCB5+ and ASC-derived conditioned media treatments lead to milder but still promising improvements. Even though further analyses have to be performed, the preliminary results obtained in this study can lay the foundations for a novel therapeutic approach with the application of cell-based therapy in CKD.